Restorative Justice as a Window Into Relationships: Student Experiences of Social Control and Social Engagement in Scotland and Canada - Reimer, Kristin Elaine (Université d'Ottawa / University of Ottawa, 2015)
The practice and popularity of restorative justice (RJ) in education has been growing in recent years. There is, however, no universal understanding of RJ and its objectives. RJ can be understood in dramatically different ways by those implementing it: as an approach that challenges taken-for-granted structures and systems of discipline and control in schools; or as simply another tool that emphasizes compliance and punishment. Little research has been conducted that makes these differences explicit, and what the impact these different understandings of RJ might have on students. This multi-site case study examined how RJ was applied, how it was understood and what its intended objectives were in two schools, set in different contexts – Scotland and Canada. Although data was collected from teachers and principals to understand the context, my primary focus was on the students, those whom RJ was most intended to affect. Through questionnaires, observations, learning circles and engaging students as co-researchers, this study situates the student experience of RJ within particular school, regional and national contexts. The study finds that RJ in schools is a window into what is most fundamental to students: relationships. Viewing relationships through the window of RJ reveals both their centrality to students and their character of being of social control or social engagement. The study argues that RJ, by itself, does not guarantee certain qualities of relationship, but it does allow us to examine those qualities and ask questions of how school relationships are used to engage and/or control.
Keywords: Restorative justice; Education; Restorative approach; Student voice; Social control; Social engagement; Scotland; Canada; Alberta; Discipline; Relationship; School climate